Effectiveness of interventions aiming at reducing sedentary behaviour in a non-surgical population with overweight or obesity: A systematic review and meta-analysis. Issue 2 (March 2019) - Zabatiero, Juliana; Ng, Leo; Clayton, Rebecca; Middlemiss, Suzanne; Kang, Kwangil; Harrold, Megan; Cavalheri, Vinicius
Abstract: Aim: This systematic review and meta-analyses of randomised controlled trials (RCTs) investigated the effectiveness of interventions to reduce sedentary behaviour amongst people with overweight or obesity. Secondarily, it aimed to investigate the effectiveness of these interventions on body mass index (BMI), time spent in moderate-to-vigorous physical activity (MVPA) and health-related quality of life (HRQoL). Methods: A search of six databases (CENTRAL, PubMed, Embase, PEDro, CINAHL and PsycINFO) was conducted from inception to July 2018. RCTs in which sedentary behaviour was measured by accelerometry or inclinometry, with participants of any age with overweight or obesity were included. Subgroup analyses were undertaken comparing studies that included adults versus children and studies with an active component (e.g., treadmill desk, physically active breaks) versus no active component to their intervention. Results: Nine studies (n = 1859) were included. Compared to the control group, the interventions significantly reduced time spent in sedentary behaviour (standardised mean difference [95% confidence interval] −0.33 [−0.59 to −0.08] overall; −0.53 [−0.95 to −0.11] in adults). Subgroup analyses demonstrated that only interventions that included active components reduced time spent in sedentary behaviour (−0.54 [−0.88 to −0.20]) and increased time spent in MVPA (1.29 [0.02 to 2.56]). Subgroup analyses demonstrated that interventions only reduced BMI in studies of children (−0.09 [−0.18 to −0.00]) and in those with no active component (−0.09 [−0.18 to −0.01]). There were insufficient data to investigate the effectiveness of these interventions on HRQoL. Conclusions: This novel systematic review and meta-analyses suggests interventions aiming to effectively reduce objectively-measured sedentary behaviour need to specifically include an active component.